Utilization of family planning services among residents of Mkar community, Gboko LGA, Benue State, Nigeria - Iba, Bemhemba (Orapuh Journal, 2020)
Introduction Family planning is an organized effort to assist people to have the number of children they want and to space them as they choose or want to. It is the key to slowing unsustainable population growth and the resulting negative impacts on the economy, environment, and national and regional development efforts. Purpose The purpose of the study was to assess the level of utilization of family planning among residents of Mkar Community, Benue State, Nigeria. Materials and methods A sample of 110 women of childbearing age was selected from the community using a purposeful non-probability sampling technique. Data was obtained using questionnaires. Descriptive statistics were used to summarise and organise data while Chi-square test was used to test for association between variables and the level of significance was set at 5% (0.05). Results The results of this study showed that 95.5% of the respondents knew about family planning, 68.2% were currently using at least one method of family planning and 40% indicated they use family planning to avoid unwanted pregnancies. Age group (p=0.737) and religious affiliation (p=0.12) were not significantly associated with the utilization of family planning while marital status (p=0.002), educational level (p=0.021), and occupational status (p=0.002) were found to be significantly associated with the utilization of family planning. Conclusion The utilization of family planning in this survey was low, despite a reported high awareness and knowledge about family planning in the study area. There is, therefore, a need for more campaign and public enlightenment programs on family planning utilization, importance, and benefits, to fast track the spread of information and further improve its utilization.